Das essayistische Bewußtsein als poetologische Grundkategorie im Schaffen von Elias Canetti - Mausch, Krzysztof (Wydział Neofilologii UAM w Poznaniu, 2016)
This book undertakes analysis of the essays of Elias Canetti: Masse und Macht , Das Gewissen der Worte and Die Provinz des Menschen. The first part is dedicated to a scientific reconstruction and description of the Canetti’s process of the literary creativeness understood as a part of communication processes. The aim of Canetti is to establish the essayistic consciousness as his basic poethological category of the literary creativeness as well as essaistically conscious orator with all personal and rhetorical features. The authors purposes in this part is to prove the Essayismus as the forth genre in the genology . The second part contains the broad analysis of Canetti’s original concept of fear for a touch of the unknown in darkness understood as a basic element of the socialization of an individual human being in the natural world of relations. The categories established by Canetti about the nature of power, death and the domestication of fear being observed in the modern world.are uncannily accurate. The main purpose of this book is to describe in the categories of an established anthropology which is to answer the questions of the moral obligations of the developing individuals to save the Humanity in the people. Canetti strips away the trappings of the civilization and depicts human beings as what we , at base, are that is animals. In the essence, our instincts that make us look for safety in crowds, follow a Big Man, jump into heaps and live in packs are similar to what we see in other mammals, especially primates.
Keywords: masa i władza; Mass (crowd) and power; Masse und Macht; paranoja; paranoia; Paranoia; śmierć i przetrwanie; death and survival; Tod und Überleben; antropologia strachu; anthropology of fear; Anthropologie der Angst; psychologia jedzenia; psychology of eating; Psychologie des Essens; język jako instrument władzy i przetrwania; language as a instrument of power and survival; Sprache als Instrument der Macht und des Überlebens; Hitler; naziści; Nazis; literaturoznawstwo; literary criticizm; Literaturwissenschaft; esej i eseizm; essay; Essay und Essayismus; Canetti